Science Learning Model in Indonesian Elementary Schools during Pandemic - Anisa Destika Sari; Ika Maryani; Islahuddin (The Indonesian Institute of Science and Technology Research, 2023)
This study aims to determine trends and recommendations for research on science learning models in elementary schools using a descriptive quantitative literature study method with a bibliometric approach. The data collection technique used is content analysis documentation. The data analysis technique in this study used Google Scholar database, Microsoft Exel and VOSviewer. The objective is to find out the trend of learning models as research topics during the 2020-2021 pandemic, namely Problem-Based Learning, Discovery Learning, Project-Based Learning, Contextual Teaching Learning and RADEC learning focusing on learning outcomes objectives, HOTS (critical and creative thinking), the effectiveness of learning media, learning motivation and understanding of science concepts. Recommendations for learning model topics for further research are Contextual Problem-Based Learning, Creative Responsibility Based Learning (CRBL), Guessing Word, Scramble, Murder, Somatic, Auditory, Visual and Intellectual (SAVI), Talking Stick, Discovery-Inquiry learning and Gallery Walk, Children Learning in Science (CLIS) with a focus on Religion, Culture and Social Attitudes. Meanwhile, based on VOSviewer, the recommendations for the learning model topic for the subsequent research are STEM education linked to religion.